The Intraperitoneal-Ketoprofen-Histopathological Induced Alterations in the Wistar Rat Kidneys - Samer Riyadh Fadhil , Hakim Bahlok Jebur2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The current-focused study was carried out to generate a data profile about expected changes that could beinduced in the kidneys of rats due to the use of intraperitoneal ketoprofen (KP). The study involved using24 adult male Wistar rats sorted randomly into four groups (six animals per group). One group was treatedas a control group, C, which was supplied with distilled water (DW) only. The remaining animals werepresented as (50KP), (25KP), or (12.5KP) groups that received 50mg/kg.b.w., 25mg/kg.b.w., or 12.5mg/kg.b.w., respectively, of KP. The experiment was continued for 70 days, and the kidney tissue sampleswere collected from the scarified animals at the end of day 70 of that experiment. The kidney tissues of the50KP animals revealed dilation of the tubules throughout the outer strip of the outer medulla with necrosisand sloughing of the epithelial cells of the proximal convoluted tubules (PCTs). However, the 25KP groupsuffered lesser grades of epithelial-cell sloughing of the PCTs with lower levels of dilation of tubules thanthose recorded in the 50KP group. On the other hand, the kidney tissues of the 12.5KP group showed onlydilation in the PCTs. The present experimental data unveil the side effects generated by the use of theintraperitoneal KP in the examined rat kidneys which should be used as a launching set of information forbetter use or further study this drug and its side effects in human patients.